Pendekatan Spasial Panel Data pada Tingkat Pengangguran Terbuka di Provinsi Nusa Tenggara Timur Tahun 2020–2023 - Haryati Mustafa (Badan Pusat Statistik Provinsi NTT, 2025)
Based on theory, low unemployment rate is expected to reduce poverty and stimulate economic growth in a region. However, this theory does not align with conditions in NTT. According to BPS (2023), NTT is the province with the seventh lowest unemployment rate but the third highest poverty rate, accompanied by low economic growth in Indonesia. This phenomenon cannot be separated from the influence of various economic and spatial factors. Each region has unique characteristics that may affect the unemployment condition of neighboring region, a concept known as spatial dependency. Therefore, this study aims to analyze the factors influencing the unemployment rate, taking into account spatial effects. The results of the SEM estimation with random effects indicate that the spatial effect is significant and positively impacts the unemployment rate at a 5 percent significance level. Other factors affecting the unemployment rate include poverty and GRDP. Meanwhile, the migration variable does not have a significant effect on unemployment rate in NTT.